Evaluation of repertories recombination protocol modification (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Neves Filho, Stella, Dicezare and Garcia Mijares (2015), developed an experimental model with the objective of observing the recombination of repertoires in rats (Rattus norvegicus). The experiment consisted of discrete, successive training on the recombination of two different repertoires: (1) digging, and (2) scaling. The solution to the problem situation consisted of digging into the second camera and climbing two flights of stairs. As a result, the animals were able to complete the task, although with topographies of different responses. Based on this experimental model, the research aimed to evaluate whether the insertion of a discriminative training procedure (Sd: sound) influences the repertoire recombination process. Because, in the original experiment, the animals underwent the pre-test phase without delimiting the relation between behavioral emission and reinforcing consequence, so it was not clear whether the problem situation that the animals were solving was indeed a problem. Ten albino rats (Rattus norvegicus) of the Wistar line were used, naive to experiment. They were randomly divided into two groups with 5 animals each: (1) experimental group, which received intervention from the Sd training, in addition to the training of digging and climbing, and (2) control group, which had its process similar to that of Neves Filho et al. (2015). Subsequently, they were submitted to a problem situation, with the issuance of Sd, in order to evaluate the performance of the animals. All animals in the experimental group solved the problem; while none of the control resolved. Based on the data, we propose that the insertion of this procedure is relevant to the repertoire recombination process, since it ensures that the subject is under control of the problem situation.
Keywords: problem solving; recombination of repertoires; discriminative training; insight